PERBANDINGAN HASIL BELAJAR SISWA YANG MENGGUNAKAN MULTIMEDIA PEMBELAJARAN INTERAKTIF DAN MEDIA PRESENTASI - Andi Setiawan; Yarmaidi Yarmaidi; Irma Lusi Nugraheni (JPG (Jurnal Penelitian Geografi), 2015)
This study aimed to: (1) investigate the difference of students pre-tests before being taught by using interactive-teaching multimedia and presentation, (2) investigate the difference of students post-tests after being taught by using interactive-teaching multimedia and presentation, (3) investigate the difference of gain between students who were taught by using interactive-teaching multimedia and those taught by presentation. The method employed in this research was true-experimental designs. The subjects were the VII grade students of e and f class. T-test was used as data analysis. The research results showed: (1) there was difference of means of pre-test between students who were taught by using interactive-teaching media and those who were taught by using presentation media at the first pre-test, but there was no difference at the second pre-test for the similar subjects, (2) there was difference of means between students who were taught by using interactive-teaching media and those who were taught by presentation media, (3) there was difference of means of gain-increase on students achievement of those who were taught by using interactive-teaching multimedia and those who were taught by presentation media.Penelitian ini bertujuan untuk mengetahui: perbedaan pretes siswa sebelum diajar menggunakan multimedia pembelajaran interaktif dan presentasi, (2) perbedaan postes siswa setelah diajar menggunakan multimedia pembelajaran interaktif dan presentasi, (3) perbedaan gain belajar siswa yang diajar menggunakan multimedia pembelajaran interaktif dan presentasi. Metode yang digunakan true-experimental designs. Subjek penelitian adalah siswa kelas VII.e dan VII.f. Analisis data menggunakan Uji-t. Hasil penelitian menunjukan: (1) terdapat perbedaan rata-rata pretes pertama antara siswa yang akan diajar menggunakan multimedia pembelajaran interaktif dan media pembelajaran presentasi, sedangkan pada pretes kedua tidak terdapat perbedaan, (2) terdapat perbedaan rata-rata postes siswa yang diajar menggunakan multimedia pembelajaran interaktif dan media presentasi. (3) terdapat perbedaan rata-rata gain hasil belajar siswa yang diajar menggunakan multimedia pembelajaran interaktif dan media presentasi.Kata kunci: hasil belajar, media pembelajaran interaktif, media pembelajaran presentasi